Exposure to zinc oxide nanoparticles (ZnO-NPs) induces cardiovascular toxicity and exacerbates pathogenesis – Role of oxidative stress and MAPK signaling. (5th January 2022) - Nagarajan, Manigandan; Maadurshni, Gobichettipalayam Balasubramaniam; Tharani, Ganeshmurthy Kanniamal; Udhayakumar, Inbamani; Kumar, Gayathri; Mani, Krishna Priya; Sivasubramanian, Jeganathan; Manivannan, Jeganathan
Abstract: The precise toxico-pathogenic effects of zinc oxide nanoparticles (ZnO-NPs) on the cardiovascular system under normal and cardiovascular disease (CVD) risk factor milieu are unclear. In this study, we have investigated the dose-dependent effects of ZnO-NPs on developing chicken embryo and cell culture (H9c2 cardiomyoblast, HUVEC and aortic VSMC) models. In addition, the potentiation effect of ZnO-NPs on simulated risk factor conditions was evaluated using; 1. Reactive oxygen species (ROS) induced cardiac remodeling, 2. Angiotensin-II induced cardiac hypertrophy, 3. TNF-α induced HUVEC cell death and 4. Inorganic phosphate (Pi) induced aortic VSMC calcification models. The observed results illustrates that ZnO-NPs exposure down regulates vascular development and elevates oxidative stress in heart tissue. At the cellular level, ZnO-NPs exposure reduced the cell viability and increased the intracellular ROS generation, lipid peroxidation and caspase-3 activity in a dose-dependent manner in all three cell types. In addition, ZnO-NPs exposure significantly suppressed the endothelial nitric oxide (NO) generation, cardiac Ca 2+ - ATPase activity and enhanced the cardiac mitochondrial swelling. Moreover, inhibition of p38 MAPK and JNK signaling pathways influence the cytotoxicity. Overall, ZnO-NPs exposure affects the cardiovascular system under normal conditions and it exacerbates the cardiovascular pathogenesis under selected risk factor milieu. Graphical abstract: Image 1 Highlights: ZnO-NPs exposure affects vascular development. Oxidative stress, apoptosis and mitochondrial impacts are prominent during exposure. Interfering p38MAPK and JNK signaling prevents the cytotoxic response. Synergistic effects on Angiotensin II and TNF-α induced pathogenic events.